Enhanced bone regeneration via local low-dose delivery of PTH1-34 in a composite hydrogel - Zhang, Shanyong; Ding, Lei; Chen, Gaoyang; Zhang, Jiayin; Ge, Wanbao; Qu, Yuan (Frontiers in Bioengineering and Biotechnology, 2023)
Introducing bone regeneration-promoting factors into scaffold materials to improve the bone induction property is crucial in the fields of bone tissue engineering and regenerative medicine. This study aimed to develop a Sr-HA/PTH1-34-loaded composite hydrogel system with high biocompatibility.Teriparatide (PTH1-34) capable of promoting bone regeneration was selected as the bioactive factor.Strontium-substituted hydroxyapatite (Sr-HA) was introduced into the system to absorb PTH1-34 to promote the bioactivity and delay the release cycle. PTH1-34-loaded Sr-HA was then mixed with the precursor solution of the hydrogel to prepare the composite hydrogel as bone-repairing material with good biocompatibility and high mechanical strength. The experiments showed that Sr-HA absorbed PTH1-34 and achieved the slow and effective release of PTH1-34. In vitro biological experiments showed that the Sr-HA/PTH1-34-loaded hydrogel system had high biocompatibility, allowing the good growth of cells on the surface. The measurement of alkaline phosphatase activity and osteogenesis gene expression demonstrated that this composite system could promote the differentiation of MC3T3-E1 cells into osteoblasts. In addition, the in vivo cranial bone defect repair experiment confirmed that this composite hydrogel could promote the regeneration of new bones. In summary, Sr-HA/PTH1-34 composite hydrogel is a highly promising bone repair material.